Cardiovascular toxicity secondary to systemic antimonials: treatment strategies - Grisales González, Luis Felipe; Valverde Legarda, Edilberto Adrian (Medicina UPB, 2026)
Leishmaniasis is a disease of worldwide distribution and Colombia contributes significantly to this statistic. Meglumine antimoniate (Glucantime®) has classically been the treatment of choice; however, these antimonials can have a high degree of toxicity and can be potentially fatal. We present the case of an elderly patient who at the end of treatment for cutaneous leishmaniasis presented cardiac toxicity and electrolyte alterations, generating a prolonged QT syndrome with the subsequent development of multiple episodes of monomorphic and polymorphic ventricular tachycardia, requiring electric shocks and transvenous pacemaker positioning for rhythm control. The importance of this report lies in the need to recognize the signs and symptoms suggestive of toxicity and the management provided.